2003
DOI: 10.1103/physrevb.67.054414
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering study of two-magnon states in the quantum magnet copper nitrate

Abstract: We report measurements of the two-magnon states in a dimerized antiferromagnetic chain material, copper nitrate (Cu(NO3)2 · 2.5D2O). Using inelastic neutron scattering we have measured the one and two magnon excitation spectra in a large single crystal. The data are in excellent agreement with a perturbative expansion of the alternating Heisenberg Hamiltonian from the strongly dimerized limit. The expansion predicts a two-magnon bound state for q ∼ (2n + 1)πd which is consistent with the neutron scattering dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 29 publications
6
59
0
Order By: Relevance
“…3, are in quantitative agreement with the interacting two-particle Schrödinger wave functions, calculated in the appendix of Ref. 19. In particular, we resolve the spin-1 bound mode of the AHC, which is a direct signature of the two-particle interaction, given in Figs.…”
Section: A One-magnon Two-magnon and Bound Statessupporting
confidence: 72%
See 2 more Smart Citations
“…3, are in quantitative agreement with the interacting two-particle Schrödinger wave functions, calculated in the appendix of Ref. 19. In particular, we resolve the spin-1 bound mode of the AHC, which is a direct signature of the two-particle interaction, given in Figs.…”
Section: A One-magnon Two-magnon and Bound Statessupporting
confidence: 72%
“…23 Equivalent chains lie along the [1,1,1]/2 and [1,−1,1]/2 directions and project onto the same direction on the (h,0,l) plane. 19 A dilution insert provided sample temperatures down to 120 mK and a rotation stage allowed the magnetic chains to be rotated to different angles relative to the incident beam of neutrons. A white beam is pulsed at 50 Hz with neutrons arriving at the sample over the initial 34-m flight path at different times according to their energy.…”
Section: B Neutron Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of coupling between dimers, triplons usually become mobile and can hop to neighboring dimer sites. For particular cases, the thermodynamic finite temperature behavior of the mobility of these hard-core bosons has been treated using statistical models reproducing triplon band renormalization and damping observed in experiments [5][6][7][8][9]. In general, the increase of the thermal population of bosons produces an increased repulsion and a reduced mobility, which is observed as a reduction of the dispersion bandwidth.…”
mentioning
confidence: 99%
“…Using conventional INS it has been shown that copper nitrate [Cu(NO 3 ) 2 × 2.5 D 2 O], a model material for a onedimensional alternating Heisenberg chain (AHC), displays a temperature dependent asymmetric lineshape in the frequency domain [9,23,24]. The material was recently investigated in the time domain using the high resolution neutron resonance spin-echo triple-axis spectroscopy (NRSE-TAS) [25].…”
Section: Introductionmentioning
confidence: 99%